Effect of annealing on nonlinear optical properties of 70% deuterated DKDP crystals at 355 nm. Issue 45 (7th November 2018) - Cai, Dongting; Lian, Yafei; Chai, Xiangxu; Zhang, Lisong; Yang, Liming; Xu, Mingxia
Abstract : Thermal annealing decreased the nonlinear absorption and refraction, which could lead to an improvement of the laser-induced damage threshold. Abstract : Type II samples were obtained from the adjacent positions of the same crystal and annealed at different temperatures for 96 h. The nonlinear optical properties of these annealed samples, including nonlinear optical absorption (NLA) and nonlinear refraction (NLR), were measured at the third-harmonic-generation (THG) wavelength (355 nm) of a picosecond Nd:YAG laser by the Z-scan method. The NLA coefficient β and NLR index n were obtained by fitting the experimental data. According to the fitting result, the nonlinear absorption at 355 nm is identified as two-photon absorption and a nonlinear refraction index with a positive sign indicates the generation of a self-focusing effect. Our experiments showed that thermal annealing remarkably affected the nonlinear optical properties of 70% deuterated DKDP crystals. Both of the NLA coefficient β and NLR index n decrease with the increase of annealing temperature. At the optimum annealing temperature of 150 °C, the β and n of the type II THG sample were 3.5 × 10 −2 cm GW −1 and 2.31 × 10 −7 cm 2 GW −1, which were only 25% and 45% that of the unannealed sample, respectively. The laser-induced damage threshold (LIDT) was measured at the THG wavelength (355 nm) of a nanosecond Nd:YAG laser by the R-on-1 method. The effect of annealing on the LIDT and on the nonlinear optical properties showed a similar trend, indicating that the process of crystal damage is related to NLA and NLR.